2018
DOI: 10.1016/bs.aambs.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Microbial Processes in Geotechnical Engineering

Abstract: Over the last 10-15 years, a new field of "biogeotechnics" has emerged as geotechnical engineers seek to find ground improvement technologies which have the potential to be lower carbon, more ecologically friendly, and more cost-effective than existing practices. This review summarizes the developments which have occurred in this new field, outlining in particular the microbial processes which have been shown to be most promising for altering the hydraulic and mechanical responses of soils and rocks. Much of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 196 publications
0
17
0
1
Order By: Relevance
“…Engineered (bio)mineralization or ureolysis‐induced calcium carbonate precipitation (UICP) techniques (Equation [1]) have been an increasingly popular area of research for use in ground improvement, construction materials, remediation, and subsurface applications 1‐8 . In fact, ground improvement with mineralization strategies has been studied extensively resulting in a new field of study described as bio‐mediated geotechnics 2,9‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Engineered (bio)mineralization or ureolysis‐induced calcium carbonate precipitation (UICP) techniques (Equation [1]) have been an increasingly popular area of research for use in ground improvement, construction materials, remediation, and subsurface applications 1‐8 . In fact, ground improvement with mineralization strategies has been studied extensively resulting in a new field of study described as bio‐mediated geotechnics 2,9‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that the strength of bio‐cemented soils is positively related to the amount of calcium carbonate precipitated (Montoya and DeJong 2015; El Mountassir et al . 2018). Moreover higher EP can reduce the cost of application by reducing the number of injections into the biotreated ground and the content of cementation solution.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria are abundant in soil; for instance, in one gram of soil in top 1 m, there are approximately 2 × 10 9 bacteria, many of which can survive and thrive at deeper depths [105]. Over the last decade, there has been increasing attention over what microbial processes can offer to geotechnical engineering [106]. MICP is a bio-mediated process for precipitation of calcium carbonate [101], desirably at particle contact points.…”
Section: Microbial-induced Carbonate Precipitation (Micp)mentioning
confidence: 99%